Learning from the positive to reduce rural poverty: institutional innovations in agricultural and natural resources research and development - Biggs, Stephen D. (2005)
This paper argues that opportunities for reducing poverty, improving social inclusion, and influencing policy and institutional changes are being missed as a result of not learning sufficiently from development practitioners who have been effective in bringing about positive changes in the past. Cautionary tales, positive deviance, innovations systems and aid ethnographic literature is reviewed. Three agricultural and natural resources case studies of positive experiences are described. These cover the spread of bamboo tubewells in eastern Bihar, changes in rice research policy and the rice innovation system in Nepal, and the spread of groups and group based organisations and federations in Nepal. These are used to illustrate how institutional innovations at macro levels came about and gave rise to positive development outcomes. Implications for innovations theory and for rural development practice are discussed.